2003
DOI: 10.1002/pssc.200303251
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray characterization of high quality AlN epitaxial layers: effect of growth condition on layer structural properties

Abstract: .72. Dd, 68.55.Jk AlN layers were deposited directly on (0001) sapphire by a MOCVD two-step pressure process. The best (0002) and (10 12) rocking curves had FWHM values of ~360 arcsec and ~580 arcsec respectively. A detailed X-ray diffraction study was carried out to investigate the effect of growth condition on the layer structural properties. In-plane twist was estimated from the FWHM values of both ω-scans and φ-scans as functions of inclination angle, using the quasi-symmetrical reflection from a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The FWHM of the (0 0 0 2) reflection was used to estimate the tilt distribution. The ''in-plane'' crystalline quality was evaluated using off-axis ð1 0 % 1 2Þ plane rocking curves measured under quasi-symmetric configuration [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FWHM of the (0 0 0 2) reflection was used to estimate the tilt distribution. The ''in-plane'' crystalline quality was evaluated using off-axis ð1 0 % 1 2Þ plane rocking curves measured under quasi-symmetric configuration [6].…”
Section: Methodsmentioning
confidence: 99%
“…Because of the significant differences in growth rate, AlN epilayers with such ''mixed polarity'' domains exhibit rough surface morphology. We also found that the in-plane crystalline quality of these AlN layers was very responsive to the extent of substrate nitridation [6]. While the process optimization can be very reactor dependent, it is possible to identify some of the growth-related characteristics of MOCVD-grown AlN layers that appear to be controlling the crystal quality.…”
Section: Introductionmentioning
confidence: 93%
“…inclination angle w plane is used to generate a conventional plot, similar to those shown in previous reports [5][6][7]. The solid lines in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in most of the previous nitride analyses [4][5][6][7], microstrain is neglected. The justification for ignoring microstrain effects is based on the fact that lattice tilt and twist are often the most dominant broadening terms in typical heterogeneous epitaxial nitride materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation